Асиметрiя гамiльтонiана i сингулярна поведiнка довжини толмена в рамках канонiчного формалiзму - Kulinskii, V. L. (Publishing house "Academperiodika", 2019)
The connection of the asymmetry of a Hamiltonian with a critical behavior of the Tolman length is studied from the point of view of a nonlinear transformation of the order parameter. It is shown that the structure of the critical asymptotics of the Tolman length is determined by that for the asymmetric part of the isothermal compressibility. The relation to the singularity of the diameter of a binodal is proved within the canonical formalism approach. It is shown how to obtain the leading critical behavior from the exact statistical mechanics expressions for the Tolman length. The results are compared with the known results by M.A. Anisimov, Phys. Rev. Lett., 98 035702 (2007).